2021
DOI: 10.47007/jeko.v12i02.4152
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Yang Mempengaruhi Impulse Buying

Abstract: The change in buying style from offline to online has made many modern retailers unable to compete, thereby reducing sales massively in shopping centers. This situation encourages industry players to be able to find a breakthrough in increasing sales at their outlets. This study aims to determine the factors that can increase impulse buying so that it can provide an empirical basis for decision making by retailers to increase their sales intensively. Primary data were collected as many as 360 respondents with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…In addition to online reviews, external factors that can influence impulsive buying are social influence, which is a process by which individuals change thoughts, feelings, attitudes or behaviors as a result of interactions with other individuals (Haryono, 2015). Research conducted by (Hafidz &;Tamzil, 2021) Based on the research gap that has been described, it can be concluded that there are still inconsistencies between online review variables and social influence on impulsive buying, so it is necessary to present moderating variables to obtain empirical data.…”
Section: Meanwhile Researchmentioning
confidence: 99%
“…In addition to online reviews, external factors that can influence impulsive buying are social influence, which is a process by which individuals change thoughts, feelings, attitudes or behaviors as a result of interactions with other individuals (Haryono, 2015). Research conducted by (Hafidz &;Tamzil, 2021) Based on the research gap that has been described, it can be concluded that there are still inconsistencies between online review variables and social influence on impulsive buying, so it is necessary to present moderating variables to obtain empirical data.…”
Section: Meanwhile Researchmentioning
confidence: 99%